Design and implementation of transistor-based broadband microwave amplifiers using balanced and traveling wave distributed topologies operating at 4.0 GHz band - Evangelista, Carlo F. (2006)
Broadband amplifiers are some of the most widely used amplifiers today. They are used in Wireless LAN Communications, electronic warfare, radar, fiber-optic communication, satellite communication and other systems operating at microwave frequencies. Broadband amplifiers are much more complicated than ordinary RF amplifiers because they require high stability, large gain, high output power, and very low noise. The most common topologies of transistor-based broadband amplifiers are the distributed amplifier topology. This research concentrates on the transistor-based implementation of these two topologies. Our project is a design and implementation of each of the above mentioned topologies operating at the 4 GHz band. We performed simulations of our design and compared the simulations results with the actual parameters of the fabricated circuit. After the analysis of the comparison between the results, we stated the advantages and disadvantages of each topology and gave recommendations for appropriate applications for each amplifier topology.